Decipering the Molecular Mechanism of ACE2 Regulating A549 Cells - Xiao, Kun; Song, Licheng; Bai, Ying; Liu, Pengfei; Liu, Yuhong; Xie, Fei; Xie, Lixin (Frontiers in Genetics, 2021)
Angiotensin-converting enzyme 2 (ACE2) is an aminopeptidase that functions as a part of the renin-angiotensin system (RAS). The RAS pathway plays a crucial role in regulating the local blood flow within a tissue. As a consequence, the role of ACE2 in regulating vasculature properties has been widely appreciated. Additionally, ACE2 has also been reported to show anti-tumorigenic activity. However, the mechanistic basis of this function has remained largely unexplored. In the current study, using a lentivirus-based expression system in lung cancer cells (A549), we show that ACE2 overexpression reduces the viability and migratory potential of cancer cells, highlighting the robust anti-tumorigenic effects of ACE2 function. Moreover, a quantitative proteome-level comparison between ACE2 overexpressed (OE) and empty vector-controlled (NC) cells reveals a large number (227) of differentially expressed proteins (DEPs) that may have contributed to this phenomenon. Functional enrichment of these DEPs has uncovered that most of them perform binding activities and enzymatic reactions associated with metabolic pathways and various post-transcriptional gene expression regulatory mechanisms. Besides, cellular component analysis reveals that the DEPs function across a range of compartments within a cell with a relatively heterogeneous distribution. Our study, therefore, supports the previously established anti-tumorigenic effects of ACE2 overexpression in lung cancer cells. An analysis based on comprehensive, unbiased, and quantitative proteomics, we have provided a rigorous mechanistic explanation for its functions.